Climate Change and the Canadian Higher Education System: An Institutional Policy Analysis - Henderson, Joseph A.; Bieler, Andrew; McKenzie, Marcia (Canadian Journal of Higher Education, 2017)
Climate change is a pressing concern. Higher education can address the challenge, but systematic analyses of climate change in education policy are sparse. This paper addresses this gap in the literature by reporting on how Canadian postsecondary educational institutions have engaged with climate change through policy actions. We used descriptive quantitative methods to analyze climate change-specific policies from a representative sample of 50 institutions across Canada and found that nearly half had some form of climate policy. Existing policies were then qualitatively analyzed. We found that the most common form of response focused on the built campus environment, with underdeveloped secondary responses focused on research, curriculum, community engagement, and governance policies. We consider the motivations for such institutional action and end with implications for policy makers and future research.